Comparison Of Law Enforcement Against Perpetrators Human Organ Criminal Offence In Indonesia And Brazil - Muhammad Yaseen; Aureza Nurul Hikmah; Muhammad Kahfi Oktariano; M Raflyalfasya Raflyalfasya; M. Deo Alfachri (Universitas Malayati, 2025)
Study This compare approach law Indonesian and Brazilian criminal cases in handle act criminal trading humans , in particular crimes involving exploitation body human . Urgency study This lies in the importance of strengthening the legal system and enforcement law to perpetrator in overcome trading human beings who continue growing in Indonesia and Brazil in overcome trading human beings who continue developing . The research method used is approach comparative with analysis of secondary data obtained from document laws , international agency reports , and studies case from both countries. Research results show that even though Indonesia and Brazil have different approaches , both face similar challenges in enforcement law , such as weakness enforcement law , limitations funding , and low Public awareness about danger trading human beings . In Indonesia, the punishment criminal heavy given to perpetrator as a preventive measure , while Brazil is more emphasize restorative approach with a focus on rehabilitation programs for perpetrators and victims. Victim protection in both countries includes protection efforts physical , identity , assistance law , and support For testify without fear , but its implementation often constrained by limitations resources and coordination inter-agency . Conclusion from study This is although there is difference in approach law , both countries have almost similar challenges in overcome trading human beings . Rehabilitation of victims in both countries includes training skills , education and assistance economy , but need existence strengthening more carry on For give impact significant . Research This recommend improvement Work The same international , improving rehabilitation mechanisms , and strengthening coordination inter- institutional for increase effectiveness in prevention and control trading man . Keywords: Enforcement law , crime , body organs